PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBEREDHEAD TOGETHER (NHT) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DALAM PELAJARAN IPS EKONOMI POKOK BAHASAN PELAKU KELAS VIII A DI SMP NEGERI 1 MANGARAN - Nuhol Kisti; Ahmad Hafas Rasyidi (STKIP PGRI SITUBONDO, 2017)
The learning model is one of the causes that can affect the activity and student learning outcomes. During this learning is done in school pupils only listen to what is described by the teacher and it is less appropriate for the characteristics of social studies. One of the learning appropriate to the characteristics of the social studies and improvement of learning achievement is cooperative learning. In this study the authors only discuss the structural approach mode s Numbered Heads Together (NHT). Selection of structural models approach Numbered Heads Together (NHT) is because in this model the student occupies a dominant position in the learning process and the cooperation in the group with the presence of its main characters numbering so that all students are trying to understand the material being taught and each is responsible for a number of its members each. The purpose of this study was to determine the activity and student learning outcomes using learning of cooperative learning model application types Numbered Heads Together (NHT) on the subject of social studies classes of economic actors VIII A one In the SMP Negeri 1 Mangaran. The collection of data used in this study as follows : 1) observation method is used to determine the percentage of students activity levels during the learning process, 2) the test method used to determine student learning outcomes obtained from daily test results of students who performed each subject . From the results of this study, it is known mastery of learning outcomes, 3) interview or interview method is to achieve complementary data in charging attachment, 4) method is a method of supporting documentation of the method of observation. From the analysis of observations of student activity resulted in an increase in the positive . This is evidenced by the size of the average percentage of students in a discussion keaktivan likely to increase from the previous liveliness from 65,33 % to 78,22 %. Mastery learning that was obtained from the results of tests of mastery learning students increased to 92 % or from 25 students got passinggrade is 23 students and 2 students who do not complete. Thus there are two that have been achieved after the implementation of the first cycle and second cycle . In this research is the first change can be categorized some students have good behavior in following the second change is learning and improving student learning outcomes initially mastery learning students 60 % increase to 90,32 %. So the application of cooperative learning NHT (Numbered Heads Together) in social studies subject matter of economic agents can increase the activity and student learning outcomes in class VIII A 1 SMP Mangaran.